Interface conditions on postverbal subjects: A corpus study of L2 English - LOZANO, CRISTÓBAL; MENDIKOETXEA, AMAYA (Bilingualism (Cambridge, England), 2010)
This paper investigates how syntactic knowledge interfaces with other cognitive systems by analysing the production of postverbal subjects, V(erb)–S(ubject) order, in an L1 Spanish–L2 English corpus and a comparable English native corpus. VS order in both native and L2 English is shown to be constrained by properties operating at three interfaces: (i) lexicon–syntax: the verb is unaccusative (Unaccusative Hypothesis); (ii) syntax–discourse: the subject is focus (End-Focus Principle) and (iii) syntax–phonology: the subject is heavy (End-Weight Principle). We show that, since learners produce VS under the same interface conditions as native speakers, unaccusativity is a necessary but not a sufficient condition for VS production. However, learners overproduce VS and make persistent errors in their syntactic encoding. Our findings support recent proposals that these difficulties stem from problems at coordinating syntactic knowledge with knowledge from other external systems, but they suggest that the nature of such difficulties is not external to the syntax.